"Many a slip between the cup and the lip": The effect of default-based nudges on prosocial behavior and attitudes - Alexia Gaudeul; Magdalena Claudia Kaczmarek (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
Recent evidence suggests that default based nudges i.e. alterations in the decisional context, can have large effects on decision making and can be used as policy interventions to improve individual and public welfare. This paper presents the results of a controlled experiment (N = 988), designed to evaluate not only the effectiveness of a default manipulation on decision making, but also to explore how yielding or opposing a nudge intervention later affects attitudes (towards the nudge and the nudger) and behavior in a charity giving context. The results show that while the default nudge was effective at the time of application, it was not enough to change attitudes towards the nudged behavior as would be needed for long-term success. Indeed, we rather find that those who adopted an action that went against the nudge were more motivated to follow on through with this action later on than those who went with the nudge. We furthermore show that giving people more leeway in how to respond to a nudge improves acceptance of the nudge. We finally discuss the practical implications of our findings in terms of the applicability of default-based nudges as a tool for policy interventions.
Keywords: C9; D04; D12; D64; H41; 330; nudging; defaults; decision making; prosocial behavior; charity giving; behavioral economics